2018
DOI: 10.1016/j.appet.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Taste at first (person) sight: Visual perspective modulates brain activity implicitly associated with viewing unhealthy but not healthy foods

Abstract: Every day, people are exposed to images of appetizing foods that can lead to high-calorie intake and contribute to overweight and obesity. Research has documented that manipulating the visual perspective from which eating is viewed helps resist temptation by altering the appraisal of unhealthy foods. However, the neural basis of this effect has not yet been examined using neuroimaging methods. Moreover, it is not known whether the benefits of this strategy can be observed when people, especially overweight, ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 89 publications
1
22
0
1
Order By: Relevance
“…The amygdala, a brain region involved in salience and stimulus-reward learning (68) was also found in our study to have attenuated functional connectivity with the VTA following the administration of oxytocin. The amygdala has been shown in fMRI studies to respond specifically to visual food cues (69,70) with increased activity in obesity (71) predictive of future weight change (72). In our analysis we also found decreased connectivity between the VTA and hippocampus under oxytocin treatment and in response to the high-calorie visual food images.…”
Section: Discussionsupporting
confidence: 67%
“…The amygdala, a brain region involved in salience and stimulus-reward learning (68) was also found in our study to have attenuated functional connectivity with the VTA following the administration of oxytocin. The amygdala has been shown in fMRI studies to respond specifically to visual food cues (69,70) with increased activity in obesity (71) predictive of future weight change (72). In our analysis we also found decreased connectivity between the VTA and hippocampus under oxytocin treatment and in response to the high-calorie visual food images.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, in either 1PP or 3PP visual perspectives, people have to mentally simulate an egocentric visual representation of the context seen. Looking at painful situation from 1PP may be more readily processed than that from 3PP (Basso et al, 2018;Canizales et al, 2013;Vistoli et al, 2016). Some studies also found that painful situations observed in 1PP engage to a greater extent the sensory processes of pain perception comparatively to situations seen from 3PP, which may enhance neurophysiological activity and pain intensity judgments (Canizales et al, 2013;Vistoli et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings (Vistoli et al, 2016) showed the activations related to the core network of empathy for pain (i.e., aMCC and insula; Fan et al, 2011) both in the 1PP and 3PP visual perspectives. Looking at painful situation from 1PP may be more readily processed than that from 3PP (Basso et al, 2018;Canizales et al, 2013;Vistoli et al, 2016). Thus, in either 1PP or 3PP visual perspectives, people have to mentally simulate an egocentric visual representation of the context seen.…”
Section: Emma Duerden Et Al Used Quantitative Meta-analytic Methods Andmentioning
confidence: 99%
“…Similarly, the sight of lip movements appears to stimulate the auditory cortex too (Calvert et al 1997). A recent study also showed that watching the hand of someone else grasping food leads to activations in motor-related brain areas (Basso et al 2018). These studies suggest that through perceptual re-enactments, the consumer's senses might be stimulated online.…”
Section: Introductionmentioning
confidence: 93%